2014
DOI: 10.1111/1471-0307.12156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Penicillium roqueforti and whey cheese on gross composition, microbiology and proteolysis of mould‐ripened Civil cheese during ripening

Abstract: Four different types of mould-ripened Civil cheese were manufactured. A defined (nontoxigenic) strain of a Penicillium roqueforti (SC 509) was used as the secondary starter with and without addition of the whey cheese (Lor); in parallel, secondary starter-free counterparts were manufactured. Chemical composition, microbiology and proteolysis were studied during the ripening. The incorporation of whey cheese in the manufacture of mould-ripened Civil cheese altered the gross composition and adversely affected pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
2
3
2
1
Order By: Relevance
“…Chemical composition and pH of mold‐ripened cheeses after 2 days of ripening were: 54.77 ± 0.41% for moisture, 31.48 ± 0.44% for total protein, 0.97 ± 0.02% for titratable acidity, 3.91 ± 0.57% for salt contents, and 4.95 ± 0.00 for pH. The composition was in accordance with the results for 2 days old Civil cheeses reported by Cakmakci et al (). pH values estimated in this study was much lower than those of the studies performed by Cakmakci, Cetin, et al () and Hayaloglu and Karabulut (), who reported that the cheese pH after at least 3 months of ripening was around 6.0.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Chemical composition and pH of mold‐ripened cheeses after 2 days of ripening were: 54.77 ± 0.41% for moisture, 31.48 ± 0.44% for total protein, 0.97 ± 0.02% for titratable acidity, 3.91 ± 0.57% for salt contents, and 4.95 ± 0.00 for pH. The composition was in accordance with the results for 2 days old Civil cheeses reported by Cakmakci et al (). pH values estimated in this study was much lower than those of the studies performed by Cakmakci, Cetin, et al () and Hayaloglu and Karabulut (), who reported that the cheese pH after at least 3 months of ripening was around 6.0.…”
Section: Resultssupporting
confidence: 90%
“…Civil cheese is produced in the East Anatolia Region of Turkey, especially in Erzurum province (Cambaztepe, Cakmakci, & Dagdemir, ). It is produced by the addition of rennet and preacidified whey into the milk with gentle stirring (Cakmakci et al, ). Skimmed cow's milk is used for the production of the cheese and the resulting cheese is preferred by consumers with high cholesterol complaints, due to a lower level of fat (Cakmakci, Cetin, et al, ; Yazici & Dervisoglu, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the highest and lowest yeast and mould counts were recorded in the R (6.65 log cfu/g, the initial value) and P (5.91 log cfu/g, the final value) the cheeses, respectively ( Table 1). The yeast and mould counts reported in this research were higher than the values determined by Cakir and Cakmakci (2018), , Ceylan et al (2007), Tarakci et al (2005) for Tulum cheeses; however, were lower than the results determined by Cakmakci et al (2012) for mouldy Civil cheese, Cakmakci et al (2014) for mould-ripened Civil cheese, Hayaloglu and Kirbag (2007) for mould-ripened Kuflu cheese, Gobbetti et al (1997) for Gorgonzola cheese.…”
Section: Microbiological Characteristicscontrasting
confidence: 72%
“…In this study, the highest and lowest values of the dry matter, fat, fat-in-dry matter (FDM), protein, ash, salt, salt-in-dry matter (SDM) contents were recorded in the P cheese at 90 th days of ripening (57.66-31.63-54.85-3.186-20.33-4.76-3.22-5.59%, the final value) and R cheese at 1 st day of ripening (55.51-30.25-54.50-3.025-19.30-4.43-3.04-5.48%, the initial value), respectively (Table 2). In this research; the dry matter contents of samples were higher than the results determined by Sert et al (2014), Cakmakci et al (2011), for Tulum cheeses, Cakmakci et al (2012) for mouldy Civil cheese, Cakmakci et al (2014) for mould-ripened Civil cheese, were lower than the results reported by Cakir and Cakmakci (2018), Cakir et al (2016) for Tulum cheeses.…”
Section: Chemical Characteristicscontrasting
confidence: 63%
See 1 more Smart Citation